Structure-Activity Relationship for Fe(III)-Salen-Like Complexes as Potent Anticancer Agents - Zahra Ghanbari; Mohammad R. Housaindokht; Mohammad Izadyar; Mohammad R. Bozorgmehr; Hossein Eshtiagh-Hosseini; Ahmad R. Bahrami; Maryam M. Matin; Maliheh Javan Khoshkholgh (The Scientific World Journal)
Quantitative structure activity relationship (QSAR) for the anticancer activity of Fe(III)-salen and salen-like complexes was studied. The methods of density function theory (B3LYP/LANL2DZ) were used to optimize the structures. A pool of descriptors was calculated: 1497 theoretical descriptors and quantum-chemical parameters, shielding NMR, and electronic descriptors. The study of structure and activity relationship was performed with multiple linear regression (MLR) and artificial neural network (ANN). In nonlinear method, the adaptive neuro-fuzzy inference system (ANFIS) was applied in order to choose the most effective descriptors. The ANN-ANFIS model with high statistical significance (R2train=0.99, RMSE = 0.138, and Q2LOO=0.82) has better capability to predict the anticancer activity of the new compounds series of this family. Based on this study, anticancer activity of this compound is mainly dependent on the geometrical parameters, position, and the nature of the substituent of salen ligand.